MODAL SOSIAL PETANI KERAMBA IKAN DI DESA SAWAH KECAMATAN KAMPAR UTARA KABUPATEN KAMPAR - Widia Lestari; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at the keramba farmers in the village of rice paddies of Northern Kampar Kampar Sub-district. The purpose of this research is to find out how social capital and the constraints faced by the farmers in the villages of keramba Rice in the running of social capital. The theory is the theory of social capital that is put forth by the Coleman consists of beliefs, social networks, values and norms. This type of research uses qualitative descriptive method with approach case studies. The subject of the study amounted to 7 persons i.e. chairman, threasurer, secretary, members of keramba farmers, agents, sellers of seed fish, and fish feed salesman. The technique of determination of informants by using puposive technique of sampling. Data sources used are primary and secondary data sources. The data collected by the data collection techniques in the form of observation (Observation) and interview (Interview). The analysis of the data used in this research with the technique of collecting data from various sources by entering the theory used in accordance with the social phenomena. The results of this research are very important social capital within the group or organization, trust, value networks, and norms have a very important role in the running and smooth business keramba fish in the Rice Village and subdistrict of Kampar Utara Kampar Regency. Trust is an important element in the group, the form of confidence among farmers keramba i.e. by mutual borrow lend capital in running the business. Social networks that form of cooperation so as to form a network, such as between farmers keramba with agents who need each other and mutual benefit. Values and norms become the guideline for each Member farmer keramba, norms that apply to realize the smooth running and success in doing business keramba fish. Constraints faced in running social capital with the presence of conflicts or problems that occur in groups or with parties involved in running a business because there are disappointed and wronged then the relationship can be split asunder and cooperation did not go well and could be broken.Keywords: Social Capital, Farmers Keramba, Group